From poverty to prosperity - Claassen, Casper Hendrik (KDI School, 2016)
As Korea’s Seamaul Undong gains worldwide recognition, many LDCs (less developed countries) have engaged with the Korea International Cooperation Agency (KOICA) of South Korea with the hope of initiating Saemaul ODA (official development assistance) projects in their own countries. Yet, such projects are bound to fail if Saemaul Undong is not properly analyzed and merely transplanted abroad. Anachronistic, presentist, and overly optimistic thinking should be avoided in pursuing the endeavor of implementing Saemaul Undong in countries outside of Korea as the context of Saemaul Undong’s implementation is inextricably attached to its relative success, notably in terms of the sociopolitical, economic, and cultural factors that laid the groundwork for Saemaul Undong’s rapid transformation of the Korean countryside. Valid developmental principles can, however, be extracted through a thorough dissection of the anatomy of Saemaul Undong; and, it is these principles that need to be entrenched into the policy framework of any attempts to implement Saemaul Undong. Important systemic and policy determinants such as the degree of rural egalitarianism, the social integration among rural communities (i.e. social capital), population trends, agricultural support institutions, government effectiveness, and literacy rates (i.e. human capital) need to be considered alongside the human agency-linked determinants (self-help, cooperation, and diligence) emphasized by Saemaul Undong. Any effort to successfully implement SMART Saemaul Undong in South Africa will have to take into account South Africa’s unique rural dynamics, whilst facilitating the creation of inclusive value chains and encouraging smallholder-oriented innovation alongside the use of appropriate technologies. Establishing a proper institutional support framework based on the principles of learning through interaction and the formation of a local food system model will be key to this process.
Thesis(Master) --KDI School:Master of Development Policy,2016